2010
DOI: 10.1186/1476-069x-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported exposure to pesticides in residential settings and risk of breast cancer: a case-control study

Abstract: BackgroundPesticides are widely used in households to control insects and weeds. Several studies, over the past decades, have examined the possible relationship of serum concentration of organochlorine pesticides and the development of breast cancer. However, little data exists regarding an association between self-reported, residential exposure to pesticides and breast cancer risk. We, therefore, present a case-control study examining self-reported exposure to household pesticides with regard to associated ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…In contrast, other studies did not report an evidence to support a causal association between breast cancer and OCs. 26 , 27 Comparison between the present work and other studies is difficult and discrepancies may be explained by differences in biological samples used to assess exposure, target populations, study designs, and varied historical exposure levels.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, other studies did not report an evidence to support a causal association between breast cancer and OCs. 26 , 27 Comparison between the present work and other studies is difficult and discrepancies may be explained by differences in biological samples used to assess exposure, target populations, study designs, and varied historical exposure levels.…”
Section: Discussionmentioning
confidence: 87%
“…22–24 Another recent case-control study using a self-reported measure of acute exposure to fogger trucks prior to ages 14 and 20 did not find an increased risk of breast cancer. 9 Similarly, a population-based case-control study in North Carolina with self-reported measures of pesticide exposures reported no overall association between farming during ages 9–16 years old and breast cancer 20 and growing up on a farm was not related to breast cancer risk in the study.…”
Section: Discussionmentioning
confidence: 99%
“…We identified just 8 published studies that reported on nonoccupational and non-OC insecticide exposure and breast cancer. [178][179][180][181][182][183][184][185] Of these 8 reports, 4 were case-control studies [181][182][183][184] that lacked pesticide-specific exposure information and the fourth was an ecologic study in design. 185 The 3 remaining studies [178][179][180] assessed exposure to a number of specific pesticides, but overall, these studies are too few to provide a meaningfully review.…”
Section: Nonoccupational Oc Insecticide Exposure and Breast Cancermentioning
confidence: 99%